α-glucan remodeling by GH13-domain enzymes shapes fungal cell wall architecture - Anand Jacob; Alaina H. Willet; Maya G. Igarashi; Mustapha El Hariri El Nokab; Lesley A. Turner; Abdulrahman Khalid A. Alsanad; Tuo Wang; Kathleen L. Gould (Proceedings of the National Academy of Sciences, 2025)
Cell walls are critical structures of fungi, bacteria, and plants, providing mechanical strength, maintaining shape, and protecting cells from environmental stress. In the fission yeast Schizosaccharomyces pombe , the α-glucan synthase Ags1 produces α-1,3-glucan chains essential for cell wall integrity, but how these chains are further assembled into mature polymers is not understood. Here, we identify two conserved glycosylphosphatidylinositol-anchored α-amylase-like enzymes, Aah1 and Aah3, which act redundantly as key contributors to α-glucan network formation. Cells lacking both enzymes exhibit severe growth and morphological defects, including rounded shape, delayed division, and cell clumping. Using solid-state NMR spectroscopy of intact cells, we show that the double mutant cell walls have dramatically reduced α-1,3-glucan and galactomannan content, with a compensatory increase in β-glucans driven by the activation of the cell integrity pathway. These changes correlate with cell wall thickening, increased rigidity, and reduced polymer mobility and hydration. We also uncover in vivo polymorphic forms of α- and β-glucans, some of which are selectively lost or gained in the mutant cells. Our data suggest that Aah1 and Aah3 function as GH13-family transglycosylases that collaborate nonredundantly with the α-glucan synthase to build a properly organized α-glucan matrix. These findings highlight a previously unrecognized layer of complexity in fungal cell wall biosynthesis and point to GH13-family enzymes as potential antifungal targets given that related enzymes are found in many fungi.